Relative age and school achievement in primary education in the Cantabria Region - González-Vallinas, Paula; Librero, Julián; Peiró, Salvador; San Fabián, José Luis (Education Policy Analysis Archives, 2018)
In this paper, we explore the impact of birth month on the academic achievement in Spanish Language and Mathematics of primary students in grades 2, 4, and 6 in Cantabria County, in the academic years of 2009-2014. The findings show that students born in late-autumn months scored lower than their classmates, suffering, therefore, from the disadvantage of being relative younger. In general, results show that students born at the end of the year have worse academic performance and an increased probability for low student achievement, after controlling gender, grade repetition, and average school results. We insist on the importance of modifying compulsory school age grouping as well as applying a flexible date exam policy (evaluation criteria) to ensure that relative outcomes for younger children are not impacted by birth month.